Seabirds east of tierra del fuego, argentina during a 3d seismic survey - Seco Pon, Juan Pablo (2019)
In this study, we evaluate the relationship between the abundance of seabirds and the different phases of a seismic operation aimed at locating offshore oil fields and taking place in the high seas east of Tierra del Fuego in the southwest Atlantic Ocean. The composition of the bird assemblages and their abundances per species were recorded by means of counts throughout the seismic operation comprising a total of 75 seismic exploration stations between the end of August and the beginning of November 2012. At least 16 species of seabirds were identified, over 60% of which belonged to the Procellariiformes. Seabirds were more abundant during exploration operations in the absence of seismic activity (i.e. compressed air guns were not active). This was also true fortwo groups of seabirds with contrasting feeding habits (divers and surfacedivers/scavengers). Our study provides evidence of an avoidance behavior by an assemblage of seabirds to the sounds generated by anthropogenic activities in the Argentine Sea,Southwest Atlantic Ocean. Additionally, our results indicate the need for greater environmental regulation of human activities that introduce low frequency and high intensity sounds in the study area.